“I felt filled up with beauty.” Attending a classical symphonic concert improved veteran wellbeing - Marianne Vámosi; Bolette Daniels Beck; Chris Mathias Andreassen; Sanne Angel (Nordic Journal of Arts, Culture and Health)
Purpose: The study aimed to investigate the effect of a Western classical symphonic concert on mental wellbeing in war veterans compared to a general audience. Methods: A quasi-experimental pre-post measurement study assessed psychological stress with the Immediate Stress State VAS scale. The Music Experience Questionnaire captured perceived bodily, emotional, and mental changes. Findings: Twenty-one veterans and a general audience of n = 405 participated in the study. Both groups found reduced stress from before to after the concert; in the general audience, it was significant (p < .001). 47% of the veterans experienced a high-stress state before the concert compared to 19% after the concert (versus 15% and 5% in the general audience). The veterans perceived significantly more safety, relaxation, and calm after the concerts and indicated a positive bodily state and presence change. In contrast, the public emphasized the aesthetical impact of the concert. Originality: The unique contribution of this study lies in its collaboration with veterans in the organization of the concerts. This adds significant value to the study, enlightening the audience with new knowledge in an underresearched field: the impact of music experiences on the wellbeing of veterans.